Pemanfaatan Limbah Plastik Kresek dan Abu Serut Tebu untuk Campuran Aspal Hrc-Wc: The Utilization of Plastic Bags Waste and Bagasse Ash for HRC-WC Asphalt Mixtures - Arief Purnama, ikhwan; sarpawi, sarpawi; muhtadi, ahmad (Politeknik Pertanian Negeri Samarinda, 2023)
The remaining bagasse waste from sugarcane and plastic waste, which increases annually, has had an adverse impact on the environment, both on land and in the sea. In 2010 alone, 275 million tons of plastic waste were generated worldwide. Approximately 4.8 to 12.7 million tons of that waste were discarded, polluting the oceans. Indonesia, with a coastal population of 187.2 million, produces 3.22 million tons of poorly managed plastic waste annually. An estimated 0.48 to 1.29 million tons of this plastic waste is believed to contaminate the oceans.According to Ir. Rudy Setyo Utomo, M.Sc. (a researcher at the Research and Development Agency of West Kalimantan Province), from the total accumulated waste in Pontianak City, it is estimated that 66% consists of organic waste, roughly around 265 tons per day, while 34% is inorganic waste, approximately 135 tons per day. Organic waste comprises food remains, wood, branches and leaves, paper, and cardboard. The waste from bagasse ash contains a high silica (SiO2) content of around 68.5%, which can be utilized in asphalt mixtures to enhance their quality.In addition to utilizing bagasse ash waste, the writer also incorporates plastic bag waste as a substitute in the asphalt mixture. According to research, Indonesia ranks second in the world for the largest amount of plastic waste, following China. This study aims to create 18 asphalt mixture samples using bagasse waste and plastic waste. The outcomes of this research will be used to produce a related research journal. Keywords: Plastic, Sugarcane, and Asphalt